1D Supercapacitors for Emerging Electronics: Current Status and Future Directions. Issue 5 (15th July 2019) - Zhai, Shengli; Karahan, H. Enis; Wang, Chaojun; Pei, Zengxia; Wei, Li; Chen, Yuan
Abstract: 1D supercapacitors (SCs) have emerged as promising candidates to power emerging electronics in recent years because of their unique advantages in energy storage and mechanical flexibility. There are four main research fronts in the development of 1D SCs: 1) enhancing mechanical characteristics, 2) achieving superior electrochemical performance, 3) enabling multiple device integration, and 4) demonstrating multifunctionality. Here, a brief history of 1D SCs is presented and significant research achievements regarding the four fronts identified as the main pillars of the development of 1D SCs are highlighted. The current challenges of the fabrication and utilization of 1D SCs are critically examined and potential solutions are analyzed. Plus, the performance inconsistencies arising from the improper use and extreme diversity of performance evaluation and reporting methods are highlighted. Beyond, perspectives on future efforts are provided and goals regarding the four research fronts are set, to further push 1D SCs toward practical applications. The development of 1D SCs is summarized here, with existing obstacles diagnosed, corresponding solutions proposed, and future directions indicated accordingly. Abstract : 1D supercapacitors have emerged as promising candidates to power emerging electronics. There are four research fronts, including: 1) enhancing mechanical characteristics, 2) achieving superior electrochemical performance, 3) enabling multiple device integration, and 4) demonstrating multifunctionality. Recent research achievements are summarized, existing obstacles are diagnosed, corresponding solutions are proposed, and future directions are indicated.